Effectiveness of Peppermint Aromatherapy on Post-Hemodialysis Nausea in Chronic Kidney Disease (CKD) Patients - Anisa Dini; Chairul Huda Al Husna (Jurnal Ilmiah Multidisiplin, 2026)
Chronic Kidney Disease (CKD) is a progressive chronic disease that requires long-term hemodialysis; however, this procedure often causes post-hemodialysis nausea, which may interfere with patient comfort, nutritional intake, and quality of life. This study aims to analyze the effectiveness of peppermint aromatherapy in reducing nausea intensity among CKD patients after hemodialysis. This study used a qualitative descriptive method with a case study approach involving two CKD patients undergoing hemodialysis in the Bromo Ward of a Regional General Hospital in Malang City on April 14, 2026. Nausea intensity was measured using the Nausea Severity Scale (NSS) before and after the intervention. The aromatherapy intervention was administered by applying three drops of peppermint essential oil to a folded tissue, which was then inhaled for 10 minutes after the patients returned to the ward following hemodialysis. The results showed a decrease in NSS scores in both patients, namely Mrs. Y from 8 to 4 and Mrs. M from 8 to 3. These findings indicate that the menthol content in peppermint may provide gastrointestinal relaxation and stimulate the olfactory system, thereby helping to reduce nausea sensation. Therefore, peppermint aromatherapy can be used as a simple, safe, affordable, and beneficial non-pharmacological nursing intervention to reduce nausea in CKD patients after hemodialysis.